A giant plexiform schwannoma of the brachial plexus: case report - Kohyama, Sho; Hara, Yuki; Nishiura, Yasumasa; Hara, Tetsuya; Nakagawa, Tanefumi; Ochiai, Naoyuki (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
We report the case of a patient who noticed muscle weakness in his left arm 5 years earlier. On examination, a biloculate mass was observed in the left supraclavicular area, and Tinel’s sign caused paresthesia in his left arm. Magnetic resonance imaging showed a continuous, multinodular, plexiform tumor from the left C5 to C7 nerve root along the course of the brachial plexus to the left brachia. Tumor excision was attempted. The median and musculocutaneous nerves were extremely enlarged by the tumor, which was approximately 40 cm in length, and showed no response to electric stimulation. We resected a part of the musculocutaneous nerve for biopsy and performed latissimus dorsi muscle transposition in order to repair elbow flexion. Morphologically, the tumor consisted of typical Antoni A areas, and immunohistochemistry revealed a Schwann cell origin of the tumor cells moreover, there was no sign of axon differentiation in the tumor. Therefore, the final diagnosis of plexiform Schwannoma was confirmed.
Keywords: brachial plexus; giant; plexiform schwannoma